Bond strength of denture teeth to acrylic resin: effect of thermocycling and polymerisation methods - Barbosa, Débora de Barros [UNESP]; Ricardo Barao, Valentim Adelino [UNESP]; Monteiro, Douglas Roberto [UNESP]; Compagnoni, Marco Antonio [UNESP]; Marra, Julie [UNESP] (Wiley-Blackwell, 2008)
Failure of bonding between acrylic resin teeth and denture base material is a considerable problem for patients who wear complete dentures.The purpose of this study was to evaluate the bond strength between acrylic resins and resin denture teeth with different thermocycling and polymerisation methods.Microwave-polymerised (Onda-Cryl), heat-polymerised (Classico) and autopolymerising (Jet) acrylic resins and resin denture tooth (Biotone) were used. The acrylic resins were polymerised according to the following: (A) microwave - fast cycle, Onda-Cryl; (B) microwave - long cycle, Onda-Cryl; (C) microwave - manufacturer's cycle, Onda-Cryl; (T) water bath - long cycle, Classico; and (Q) bench polymerisation cycle, Jet. Twenty specimens were prepared for each polymerisation method. Ten were thermocycled, and 10 did not receive thermocycling. For the purpose of the study, a shear test was used. Data were analysed with the Kruskal-Wallis test and Dunn's multiple comparisons test (p = 0.05).Cycles B, C and T were similar (p > 0.05), and had statistically higher bonding values than cycles A and Q (p < 0.05) for the thermocycled and non-thermocycled groups. For all cycles, there were no statistically significant differences between thermocycled and non-thermocycled groups (p > 0.05), except for cycle Q (p = 0.0038).Thermocycling decreased the bond strength, but not significantly for microwave and heat-polymerised cycles. Regarding the bond strength of denture teeth to acrylic resin, the fast microwave polymerisation cycle should be avoided when polymerising Onda-Cryl acrylic resin. In addition, Jet acrylic resin is not adequate for use in denture repair.
Keywords: acrylic resins; bonding; shear strength; denture bases; tooth; artificial; thermocycling